Pre-school Teachers’ Beliefs towards Their Abilities of Teaching English to Pre-schoolers in Pahang, Malaysia - Rosli, Aisyah Khaleeda; Radzuan, Noor Raha Mohd (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2020)
In the education sector, teachers serve as the most important role model in improving learners' English language competency. Due to this, the beliefs of the pre-school teachers initiate a critical indicator in deciding if, given the circumstances, pre-school children can receive adequate English inputs and exposure at their age. In this study, 60 private pre-school teachers were given a set of questionnaires consisting of 14 items to investigate their beliefs towards their abilities of teaching English to pre-schoolers in Pahang, Malaysia. The findings of this study revealed a much more positive view of teachers’ beliefs in pre-school English teachings. This can become a stimulus for the growth of English proficiency among Malaysian children and consequently improve the standard of English in Malaysia in the future.